DENTIST RESPONSIBILITIES USING DENTAL PHOTOGRAPHY IN SOCIAL MEDIA - Mokhamad Khoirul Huda; Andika Persada Putera; Onge Margareth Hendro (FKG Unlam, 2022)
Background: Information and communication technology develops very rapidly along with the development of the globalization era. Photography is a mixture of art and technology that is not merely a record of the real world but is a complex piece of art that gives meaning. In the world of dentistry, dental photography is one of the tools that can facilitate the imaging process of the patient. Dental photography can be a tool for legal documentation, enforcing diagnosis, determining treatment plans, facilitating the communications between dentists and laboratories, educational facilities, and consulting equipment with laboratories. Natural, beautiful, and interesting have a subjective meaning for every human being. The dentist’s obligation is to understand what each patient wants and can lead the ideal thing for the patient. Nowadays many dentists are uploading the results of work to social media. Purpose: The purposes of this writing are to provide explanation about the legality of dental photography and dentist reasonability in using dental photography in social media. Method: The research method used is normative juridical. Results: The dentist must keep the confidentially of the document or the patient’s data, thereby avoiding document leakage that may be denied by the person who has no right. Conclusion: In Indonesia, we must comply with the law of dental photography, which is subject to the ITE laws, Health Law, Medical Practice Act, and other legal regulations.